The efficacy of tissue factor −603A/G and +5466A>G polimorphisms at the development of venous thromboembolism in cancer patients - Eroğlu, A.; Ceylan, G.G.; Ozturk, E.; Yalcin, A.; Yalcin, B.; Karasoy, D. (Experimental Oncology, 2016)
Background and Aim: Venous thromboembolism (VTE) is one of the most common complications in cancer patients. Although factor V Leiden (FVL) is the most common genetic defect causing thrombosis, the impact of gene abnormalities on thrombotic tendency in cancer patients remains poorly explored. Tissue factor (TF) is a major physiologic initiator of blood coagulation. This is the first study regarding the association of TF gene −603A/G and +5466A>G polymorphisms with VTE in malignancy. Materials and Me thods: The study consists of two groups: cancer patients with VTE were included as Group 1 (n = 46); Group 2 comprises 196 cancer patients without VTE. Restriction fragment length polymorphism method was used for the detection of polymorphisms of TF −603A/G in the 5՛upstream region and TF 5466A/G in intron 2. FVL, PT G20210A and MTHFR C677T polymorphisms were determined by using commercially available Light Cycler kits. The genotype and allele frequencies between the groups were compared using χ² or Fisher exact test, if appropriate. Results: No differences were observed in the distribution of TF gene −603A/G genotype frequencies between the groups. Although a slightly increased incidence of +5466GA genotype was in Group 1 (17.4% vs 11.2%), it did not achieve statistical significance. The prevalence of FVL was significantly greater in Group 1 compared with Group 2 (41.3% vs 4.1%, p < 0.05). Difference in frequency of 677TT+CT (MTHFR) + 5466GG (TF) genotypes combination was found in women of two investigated Groups (p < 0.05). No differences were also in genotypes and allele frequencies of MTHFR C677T and PT G20210A between two Groups (p > 0.05). Conclusions: The present study did not show significant association of TF gene −603A/G and +5466A>G polymorphisms with VTE in malignancy, however, further larger studies including different ethnic population are needed to confirm our findings.